Composite electrode modelling and optimization for solid oxide fuel cells. (13th July 2012) - Wen, H.; Ordonez, J. C.; Vargas, J. V. C.
SUMMARY In a solid oxide fuel cell (SOFC), the electrode is a composite porous structure, which can be considered to be made of ionic conductor material, electronic conductor material and pores that function as channels for the flow of reacting gases. This article proposes a model for the composite electrode of an SOFC, suitable for optimization. The model can be used to study the effects on fuel cell performance of pore diameter, porosity and tortuosity, electrical conductivity, ionic conductivity, electrode temperature, inlet reacting gas pressure, diffusivity and activation energy for the reaction. The article illustrates the use of the proposed model to find an optimal thickness of the active reaction layer by the minimization of total potential losses, or alternatively by the maximization of the fuel cell net power output. A three‐way single SOFC optimization was conducted with respect to the active reaction layer thicknesses at both electrodes, operating temperature and electrode porosity, showing that the SOFC net power density varies approximately by factor of 2, which stresses the importance of the developed model for SOFC design and optimization. This work provides a way to incorporate aspects of the electrode composition and microstructure in the evaluation of the fuel cell performance. For the ranges of electrode active reaction layer thicknesses studied in this article, the variation of net power density reached 16% at T = 973 K and 11% at T = 1173 K in the two‐way optimization. Regarding porosity, in the three‐way optimization, the net power density variation reached 10% at T = 1073 K. Therefore, the cumulative effects in the three‐way optimization for a fixed temperature show that net power density can vary approximately by 20%. Copyright © 2012 John Wiley & Sons, Ltd.